The diagnostic utility of ancillary CD117 immunomarker compared with cell block cytology of thyroid lesions based on Bethesda grading system - khoso, Muhammad Yousif; Fahim, Amin; Qureshi, Aneela; Ali, Syed Naqeeb (International Journal of Research in Medical Sciences, 2018)
Background: This is a cross sectional multicenter study carried out from July 2017 to December 2017. The aim of the present study is to evaluate the fine needle aspiration cytology and cell block of thyroid lesions on the basis of Bethesda grading system. Also, expression of CD117 immunostaining in thyroid lesions was evaluated. Finally, the results of cell block were compared with expression of CD117 immunomarker for diagnostic confirmation of different thyroid lesions. Methods: Total one hundred (100) patients presenting with thyroid swelling underwent fine needle aspiration, cell block preparation to diagnose and categorize thyroid lesion on the basis of Bethesda grading system and finally immunostaining with CD117 was carried out. Results: FNAC results showed 71% patients with benign thyroid morphology and about 23% cases were categorized as atypical to fairly malignant. In cell block study benign lesions diagnosed were 77%, 17% cases as suspicious and 6% were malignant thyroid nodules. Whereas expression of ancillary CD117 immunomarker, confirmed 83% as benign lesions and 17% cases as malignant. Overall ancillary CD117 immunomarker established the better diagnosis to manage and differentiate thyroid lesions. Conclusions: Cell block results are more accurate than FNAC in thyroid patients. The CD117 immunomarkers can be used as better diagnostic tool for confirmation of thyroid lesions and thus it can reduce unnecessary surgical intervention.